(untitled) (Ius Novum, 2024)
Effective protection of environmental resources is not possible without using instruments typical of financial law. It requires the use of State and local government public funds, which are collected and spent in the manner prescribed by law. The Environmental Protection Law regulates the various legal-financial instruments used to fulfil the protection purpose. It also contains a provision defining what financial-legal measures are in terms of this Act. The legal definition is formulated in a way that raises numerous editing and interpretation doubts. This article aims to demonstrate the accuracy of the thesis that there are defects in the statutory definition of legal and financial measures for environmental protection.